Teknologi Mini Pabrik Gaplek Menggunakan Kontrol Jarak Jauh Mendukung New Normal Covid 19 di Kecamatan Tambang Kabupaten Kampar Provinsi Riau - Juandi M; Syahril Syahril; Gimin Gimin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The potential of agro-industry made from agricultural products, in this case cassava, in Tambang District, Kampar Regency is very much evidenced by the emergence of SMEs engaged in agro-industry. This enormous potential has led to the growth of SMEs for community groups to take advantage of these opportunities in the Gaplek production business. Furthermore, this potential is an opportunity for the growth of Business Groups in the area. The Gaplek Maju Bersama Business Group consists of 20 farmers. This Gaplek business can increase the income of farmers, because cassava if sold in the market costs only Rp. 350 per kg, whereas if it is in the form of Gaplek it can reach a price of Rp. 2000/Kg. The current condition of Gaplek production is very little because there is no technology for making Gaplek, so that production only reaches 300 kg to 400 kg per day, this too depends on the weather. The purpose of this activity is to create a mini factory for making Gaplek with a production capacity of 1 ton/day by applying long-distance system technology based on biomass energy, which is very well applied in the new normal conditions of Covid 19. The method used in this activity is to design industrial control system technology. The long distance applied in the manufacture of the Gaplek mini factory will reduce contact time between workers, this is in accordance with new normal conditions. The results obtained from this activity are in the form of technological tools for the manufacture of mini cassava factories that have been implemented in Maju Bersama UKM in Tambang District, Kampar Regency, Riau Province, and have been proven to increase the efficiency of drying time only takes 3 to 5 hours depending on the size of the raw material. cassava to be dried.